Reproductive performance and diving behaviour share a common sea‐ice concentration optimum in Adélie penguins (Pygoscelis adeliae). (20th July 2018) - Le Guen, Camille; Kato, Akiko; Raymond, Ben; Barbraud, Christophe; Beaulieu, Michaël; Bost, Charles‐André; Delord, Karine; MacIntosh, Andrew J. J.; Meyer, Xavier; Raclot, Thierry; Sumner, Michael; Takahashi, Akinori; et al.
Abstract: The Southern Ocean is currently experiencing major environmental changes, including in sea‐ice cover. Such changes strongly influence ecosystem structure and functioning and affect the survival and reproduction of predators such as seabirds. These effects are likely mediated by reduced availability of food resources. As such, seabirds are reliable eco‐indicators of environmental conditions in the Antarctic region. Here, based on 9 years of sea‐ice data, we found that the breeding success of Adélie penguins ( Pygoscelis adeliae ) reaches a peak at intermediate sea‐ice cover ( ca . 20%). We further examined the effects of sea‐ice conditions on the foraging activity of penguins, measured at multiple scales from individual dives to foraging trips. Analysis of temporal organisation of dives, including fractal and bout analyses, revealed an increasingly consistent behaviour during years with extensive sea‐ice cover. The relationship between several dive parameters and sea‐ice cover in the foraging area appears to be quadratic. In years of low and high sea‐ice cover, individuals adjusted their diving effort by generally diving deeper, more frequently and by resting at the surface between dives for shorter periods of time than in years with intermediate sea‐ice cover. Our study therefore suggests that sea‐ice cover is likely to affect the reproductive performance of Adélie penguins through its effects on foraging behaviour, as breeding success and most diving parameters share a common optimum. Some years, however, deviated from this general trend, suggesting that other factors (e.g. precipitation during the breeding season) might sometimes become preponderant over the sea‐ice effects on breeding and foraging performance. Our study highlights the value of monitoring fitness parameters and individual behaviour concomitantly over the long‐term to better characterize optimal environmental conditions and potential resilience of wildlife. Such an approach is crucial if we want to anticipate the effects of environmental change on Antarctic penguin populations. Abstract : In the region around the Dumont d'Urville research station in Antarcica, when sea ice covers approximately 20% of the Adélie penguins' foraging area, we found that breeding success reaches a peak, and that most diving parameters reach an optimum for similar sea‐ice conditions, suggesting that sea ice affects the reproductive performance of Adélie penguins through its effects on diving activity.